The Information Content of Prices in Derivative Security Markets - Scott, Louis (IMF Working Papers; Working Paper ;, 1991)
Prices in futures markets and option markets reflect expectations about future price movements in spot markets, but these prices can also be influenced by risk premia. Futures and forward prices are sometimes interpreted as market expectations for future spot prices, and option prices are used to calculate the market's expectations for future volatility of spot prices. Do these prices accurately reflect market expectations? The purpose of this paper is to examine the information that is reflected in futures prices and option prices. The issue is examined by reviewing both the relevant analytical models and the empirical evidence.